SISTEM INFORMASI PENJUALAN SEMBAKO DI TOKO KARANGTARUNA TAMBAKBAYAN - , APRILIA ELKE DAMAYAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Karangtaruna Tambakbayan is a groceries store, which became one of the Karangtaruna Tambakbayan work program in Tambakbayan village. Karangtaruna Tambakbayan sales system still uses a conventional system with sales and inventory management are still recorded by hand. Errors in the calculation of counting stock and transactions are still common. Based on the problem above, information system has been built which could process sales data by using programming language such as HMTL, PHP, CSS, Javascript, Jquery, and database MySql. The sales information system could be used for controlling sales data in Karangtaruna Tambakbayan store. They could also produces the product information, sales information, and news information.